Oxidative stress and inflammation mediate the association between Life's Crucial 9 and biological ageing: A secondary analysis of two observational studies - Haoran Wang; Jingwen Zhang; Jiaxin Ning; Yating Cui; Huimin Hou; Ming Liu; Jianyong Liu; Runhua Tang; Jianye Wang (The Journal of Nutrition, Health and Aging)
Background: Life’s Essential 8 (LE8) is known to have a negative correlation with biological aging, while the relationship between the Life’s Crucial 9 (LC9) score, which includes mental health, and biological aging remains to be further investigated. Methods: We obtained data from two national cohorts, the UK Biobank and National Health and Nutrition Examination Survey (NHANES), to analyze the association between LC9 and biological aging. Biological aging was assessed using PhenoAge and KDMAge, with gender, race, and other indicators included as covariates. We applied linear regression models and restricted cubic splines (RCS) to analyze and describe the relationship. Furthermore, we explored the mediating role of oxidative stress and inflammation in the association between LC9 and biological aging. Subgroup analyses were conducted using multiple linear regression models, and differences between subgroups were assessed through interaction p-value tests. Sensitivity analyses were subsequently performed, followed by an exploration of the underlying mechanisms. Results: In this study, the UK Biobank cohort included 46,599 participants, with 44,973 participants having complete data for all covariates, LC9, and the necessary calculations for PhenoAge and KDMage. In the NHANES cohort, these numbers were 11,726 and 5,936, respectively. In the UK Biobank cohort, a significant association was found between the LC9 score and PhenoAge (β = −2.484, p < 0.001), with similar results observed for KDMage (β = −7.987, p < 0.001). Similar findings were observed in the NHANES cohort, with significant associations between the LC9 score and both PhenoAge (β = −5.327, p < 0.001) and KDMAge (β = 11.826, p < 0.001). These findings align with previous research suggesting that higher LC9 scores are associated with slower biological aging. After multivariable adjustment, an ''inverse L-shaped'' relationship was observed (non-linear P < 0.001). In the mediation analysis, oxidative stress and inflammation showed significant mediating effects between LC9 and both PhenoAge and KDMage (p < 0.001 for both). In the subgroup analysis, the LC9 score showed broad applicability, particularly among male participants aged over 60 years. Conclusion: This cohort study suggests that higher LC9 scores are associated with slower biological aging. In addition to emphasizing diet and lifestyle habits, the role of mental health in biological aging should not be overlooked.